Responding to the food, fuel and financial crises of 2009: A case for pro-poor stabilization policy - Mendoza, Ronald U (Archīum Ateneo, 2009)
Adverse shocks to poor households can cause significant long-term damage to their well being. This column argues that stabilisation policies ought to make protecting vulnerable families and children from shocks a central priority rather than ad hoc and ancillary in development strategies. Countries’ future economic growth and human development are at stake.